Seni Sebagai Katalisator Ekonomi Desa Kondongia: Strategi Pengembangan Pariwisata di Kabupaten Muna - La Ode Andi Hermawan; Wa Ode Sartika; Sarniati (Jurnal Honai, 2025)
This study explores the role of art as a catalyst for the village economy through the development of culture-based tourism in Kondongia Village. The study identifies how art can serve as a driving force for economic growth through the cultural tourism sector by encouraging active community participation. A qualitative approach was employed, with data collected through interviews with village government officials and local community members. The results indicate that local arts and culture are the main attractions for tourists, offering not only natural beauty but also meaningful cultural experiences. The concept of creative tourism, which emphasizes collaboration between tourists and the local community, enhances the added value of tourism products and strengthens the village economy. Community involvement in the development of cultural tourism spaces is essential for cultural preservation and generating significant economic benefits. Furthermore, the creative economy contributes to the creation of new business opportunities and the promotion of local culture in the global market. The tourism potential of Kondongia Village, combining cultural and natural assets, can be strengthened through collaboration with neighboring villages that possess historical sites and effective marketing strategies.